Treatment of methylene blue-containing wastewater using microorganisms supported on granular activated carbon under packed column operation - Soon-An, Ong; Toorisaka, Eiichi; Hirata, Makoto; Hano, Tadashi (Springer-Verlag, 2009)
Link to publisher's homepage at http://www.springerlink.com